Advances in clinical estimation of foetal weight before delivery - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Accurate estimation of foetal weight is of paramount importance before delivery. Clinical estimation of foetal weight is an important and necessary skill in management of obstetrics patients because of its simplicity; and if it is found to be as accurate as sonographic measurement as some studies suggest, it may be considered for screening of foetal weight especially in low-resource settings where ultrasound is unavailable. The aim of this review is to search for various literatures where clinical methods of foetal weight estimation were used and to examine these methods critically for possible recommendation for their use among obstetrics residents and healthcare practitioners. Electronic search of Medline, Pub Med, Health Internetwork Access to Research Initiative (HINARI) and Google Scholar databases from 1953 to 10th December 2014 was conducted for studies which compared clinical and sonographic foetal weight estimation. Various formulae have been suggested by researchers over the years. The methods however depend on the clinical dexterity of clinicians’ and not on specific measurements. No simple and easily applied formula has yet been suggested to transform an external maternal measurement into an estimated foetal weight. Researchers on estimation of foetal weight should work towards a consensus and reproducible formula for clinical foetal weight estimation. Symphysio fundal height (SFH) measurement with a tape-measure seems a simple clinical method because it is cheap, readily available, non-invasive and acceptable to patients. These skills should be practiced by senior obstetricians and taught to midwifes, house officers, medical officers and obstetrics residents. It is however subjected to various degrees of intra-observer and inter-observer errors and studies comparing the different formulae are lacking. Therefore, further researches are needed to improve reliability and reproducibility of these clinical methods. The reliability of other clinical methods other than Dare’ method should also be explored.